(untitled) - Kosko, Bart (New York, 1993)
Kosko , an engineering professor at the University of Southern California, makes a provocative new scientific paradigm intelligible to the general reader. Fuzzy logic posits a world in which absolutes, such as those implied in the words "true" and "false , " are less important and interesting than the matters of degree between them. "Fuzziness is grayness," and "the truth lies in the middle," according to Kosko, one of the pioneers of fuzzy logic theory, which he persuasively presents as a world view rooted more in Buddhist and Taoist assumptions than in the dichotomous Aristotelian tradition. He proposes FATs (Fuzzy Approximation Theorems) for the existence (and non-existence, as fuzziness demands) of God and as models of the abortion debate. In consumer terms, fuzzy logic is behind such "smart" machines as air conditioners and microwave ovens that gauge their operation to the conditions and demands of a given moment's task. Writing with style and risk, Kosko challenges assumptions, not about the existence of scientific authority, but about its nature.
Keywords: Logic,Fuzzy systems